Interaksi Demokratis Dalam Pembelajaran Eksploratif Fenomena Perubahan Suhu Udara dan Suhu Tanah - Pangkey, Galatiano; Tulandi, Djeli Alvi; Lolowang, Jimmy (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
The purpose of this study is to explore the concept and scientific process of the phenomenon of changes in air temperature and soil temperature in vegetation land, open land, and asphalt roads. This study uses a qualitative and quantitative approach. The exploratory research used by the research team is themodel Higher Orther Thinking Learning in Democratic Interactionwhich (HOTL-DI) Type A emphasizes interactive components, individualistic high-level learning processes and democratic interactions as a process of sharing and cooperation between individuals in groups. The first stage of object exploration (changes in air temperature and soil temperature in vegetation land, open land, and asphalt roads), concepts and scientific processes is carried out by the research team under the guidance of the thesis supervisor. The second stage is exploratory research on fourth semester students majoring in physics education for the 2021 academic year. The stage of exploring physics objects, concepts and processes in groups as democratic interactions. Democratic indicators, formulated by researchers based on the condition of group interaction when exploring objects and discussing in group report preparation. Students experience difficulties at the beginning of exploration activities because they lack experience in exploring physical concepts and processes about natural phenomena. Democratic behavior and exploration activities seem to be getting better over time, so this learning can realize learning activities to explore objects, concepts and science processes in democratic interaction learning well.